(3eHGOF eMGSHI GdJcGdja (B((3c(B4) /s - (3GdWMGf(B;(3aQGL, KfGA YWjI, eMeO GHh GdYdGs ((3GdbGgQI (B: s (3eWHYI eQcR GdJYdje GdeaJhM(B, s, 1998)
(3fXGe GdJcGdja (B- (3Gdeaghe h GdCgOGa , ebheGJ fXGe GdJcGdja h GdYhGed GdeDKQI aj JUejeg ,GdeMGSHI Yf JcdaI GdeSJdReGJ GdSdYjI GdhGQOI , GdeMGSHI Ydi JcdaI GdeSJdReGJ GdSdYjI GdefUQaI , GdeMGSHI Yf JcdaI GdYed , JMdjd YfUQ JcdaI GdYed , GdeMGSHI Yf GdJcGja ZjQ GdeHGTQI h CSS JhRjYgG , WQb JhRjY JcGdja eQGcR GdNOeGJ GdGfJGLjI Ydi GdeQGcR GdeSJajOI , eYLdGJ JMejd GdJcGdja ZjQ GdeHGTQI (B. s
Keywords: (3GdGLhQs; (3GdJcGdjas; (3GdeMGSHI GdeGdjIs